A CONSTRUÇÃO DAS NOTÍCIAS PELAS ASSESSORIAS DE IMPRENSA DA TERRA DE DIREITOS, CONECTAS DIREITOS HUMANOS E JUSTIÇA GLOBAL - Gomes, Cléber Moletta (2016)
This research studies the construction of the news by the human rights organizations's press offices Terra de Direitos, Justiça Global and Conectas Direitos Humanos. For this, the paper analyzes the media coverage held by the press offices of the institutions in three events. The research is based on the press relations's concepts, theories of constructionist perspective about journalism and the media coverage's concept. The method used was discourse analysis, focusing on a qualitative approach of the study object. They evaluated the appropriation strategies of journalistic discourse in the construction of news, considering the mediatized environment circulation and generating directions. It was found that the institutions take ownership and betting on journalistic discourse as a way to midiatizar their actions and provide directions in a traffic environment. The political and ideological positioning of entities is considered inthe definition of discursive strategies. The news of the construction of journalistic techniques are appropriate by the assessors. Their discursive offers betting on different possibilities in the appropriation and generation of directions. With this research, we hope to contribute with studies on the role of the press offices of human rights organizations in the face of intense media coverage in social discourses.